Síntese, caracterização e cinética da decomposição térmica dos materiais cerâmicos PrMO3 (M = Ni ou Co) - Aquino, Flávia de Medeiros (2010)
In this work have been studied the preparation, characterization and kinetic study of decomposition of the polymerizing agent used in the synthesis under non-isothermal condition ceramics PrMO3 of general formula (M = Co and Ni). These materials were obtained starting from the respective metal nitrates, as a cations source, and making use of gelatin as polymerizing agent. The powders were calcined at temperatures of 500°C, 700°C and 900°C and characterized by X-ray Diffraction (XRD), Thermogravimetric Analysis (TG / DTG/ DTA), Infrared Spectroscopy (FTIR), Temperature Programmed Reduction (TPR) and Scanning Electron Microscopy (SEM). The perovskite phase was detected in all the X-rays patterns. In the infrared spectroscopy observed the oxide formation as the calcination temperature increases with the appearance of the band metal - oxygen. The images of SEM revealed uniform distribution for the PrCoO3 and particles agglomerated as consequence of particle size for PrNiO3. From the data of thermal analysis, the kinetics of decomposition of organic matter was employed using the kinetics methods called Model Free Kinetics and Flynn and Wall, in the heating ratios 10, 20 and 30° C.min-1 between room temperature and 700°C. Finally, been obtained the values of activation energy for the region of greatest decomposition of organic matter in samples that were determined by the degree of conversion (α)